Is Intestinal Bacterial Diversity Enhanced by Trans-Species Spread in the Mixed-Species Flock of Hooded Crane (Grus monacha) and Bean Goose (Anser fabalis) Wintering in the Lower and Middle Yangtze River Floodplain? - Zhuqing Yang; Lizhi Zhou (Animals, 2021)
Diversity of gut microbes is influenced by many aspects, including the host internal factors and even direct or indirect contact with other birds, which is particularly important for mixed-species wintering waterbird flocks. In this study, Illumina high-throughput sequencing was used to analyze the intestinal bacteria of the hooded crane and bean goose whose niches overlap at Shengjin Lake. We tested whether contact time enhances the trans-species spread of gut bacteria. Results indicate alpha-diversity and microbial composition displayed significant separation between the two hosts in every wintering period, although the number of bacteria types shared increased with increasing contact time. For the same species, with the lengthening of contact time, alpha-diversity and the number of operational taxonomic units (OTUs) in the host intestine augmented, and the common OTUs and structural similarity of microflora in the middle and late periods were more than in the early and middle periods. In addition, we found a very high proportion of shared pathogens. Our results indicate that, although intestinal microflora of different species were separated, direct or indirect contact in the mixed-species flock caused the spread of gut bacteria trans-species, indicating that more attention should be paid to intestinal pathogens in wild birds.